HIV self-testing adoption and post-test linkage to care among men who have sex with men in China: a nationwide cross-sectional survey - Yang, Fan; Zhao, Peizhen; Tang, Weiming; Tucker, Joseph D.; Xu, Wenqian; Wang, Cheng (BMC infectious diseases, 2024)
HIV self-testing (HIVST) was recommended to improve HIV testing services. China initiated some of the first HIVST pilots in the world, providing a unique opportunity for implementation research. We aim to investigate HIVST adoption and its following linkage to care among Chinese men who have sex with men (MSM). Data were collected using an online questionnaire distributed on major social media platforms in 2018, one year after HIVST was officially endorsed and allowed for sale. MSM who were at least 16 years old, assigned as male at birth, and ever tested for HIV were eligible. Primary outcome, adoption was defined as ever use of HIVST. Bivariate and multivariable logistic regressions were performed to explore the association between HIVST adoption and sociodemographic and behavioral factors. Linkage to care was also described via the following sequential events as indicators: (1) receiving result after recent test (2), seeking care from healthcare facility if test result was positive or indeterminate, and (3) delayed time before seeking care. A total of 540 participants were included with an average age of 27.4 ± 6.6. Most were never married (87.4%) and half completed college (52.2%). Overall, 75.2% had adopted HIVST. Self-test kits were commonly obtained from community-based organizations (54.4%) and from online (46.6%). HIVST adoption was positively associated with having college or higher education (OR = 1.66, 95%CI: 1.07-2.57), and negatively associated with age older than 30 (AOR = 0.52, 95%CI: 0.32-0.84). Adoption was not associated with other socio-demographic or behavioral factors. After receiving HIV-positive or indeterminate results, 25/25 of HIVST adopters sought care while 3 out of 7 (42.9%) non-adopters sought care (p < 0.001). Delays before seeking care were not significantly different between HIVST adopters compared to non-adopters (P = 0.366). Many MSM adopted HIVST shortly after its launch. Our findings suggested that HIVST linkage to care is promising among MSM in China. Integration of HIVST with other essential sexual health services is needed.